2009
DOI: 10.1002/ijc.24608
|View full text |Cite
|
Sign up to set email alerts
|

Mre11 inhibition by oncolytic adenovirus associates with autophagy and underlies synergy with ionizing radiation

Abstract: New treatment approaches are needed for hormone refractory prostate cancer. Oncolytic adenoviruses are promising anti-cancer agents, and their efficacy can be improved by combining with conventional therapies such as ionizing radiation. The aim of this study was to determine the timing of oncolytic adenovirus treatment with regard to radiation and study the mechanisms of synergy in combination treatment. Prostate cancer cells were infected with oncolytic adenoviruses, irradiated and synergy mechanisms were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…Previous research has shown that oncolytic adenoviruses can be successfully combined with more conventional cancer treatments i.e., chemotherapy 28 and radiotherapy. 29 Further studies are needed to elucidate the underlying mechanism behind the increased efficacy of the combination of TIL and oncolytic adenovirus in vitro. Superior tumor cell killing with the combination of CAR T-cells and Ad5-D24 was recently reported to be associated with accelerated caspase pathways in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that oncolytic adenoviruses can be successfully combined with more conventional cancer treatments i.e., chemotherapy 28 and radiotherapy. 29 Further studies are needed to elucidate the underlying mechanism behind the increased efficacy of the combination of TIL and oncolytic adenovirus in vitro. Superior tumor cell killing with the combination of CAR T-cells and Ad5-D24 was recently reported to be associated with accelerated caspase pathways in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, autophagy is a decisive factor between cell death and survival, and can be either protective or lead to autophagic cell death. Notably, the induction of autophagy enhances the effects of radiation (15)(16)(17)(18)(19)(20)(21)(22). However, the contribution of autophagy to radiation efficacy remains unclear, particularly in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with recombinant adenoviruses expressing E4orf6, E4orf3, and E1B55K 24 h before irradiation significantly increases cell killing in vitro Radiation doses were selected according to relative sensitivity to radiation of each cell line (9,18). RT alone or combined with replication-deficient control virus Ad5(GL) did not affect cell viability at treatment with 8 Gy (Fig.…”
Section: Recombinant Adenoviruses Rade1b55k Rade4orf3 and Rade4orf6mentioning
confidence: 99%
“…Whole-body irradiation was used for the mice to avoid the need for anesthesia. For cell lines, in vitro radiation doses were chosen according to the relative sensitivity of each cell line, respectively (9,18).…”
Section: Irradiation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation